A Spectrophotometric Method for the Quantitative Estimation of Trimethoprim via Oxidation and Decolonization of the Indigo Carmine - Abdulla M. Sulaiman; Khalida M. Omar (African Journal of Advanced Pure and Applied Sciences, 2022)
The aim of this investigation was to develop a simple, rapid and sensitive spectrophotometric method for the determination of trimethoprim in bulk and pharmaceutical dosage forms. The suggested method based on the oxidation of trimethoprim with known excess of oxidizing agent (N-bromosucinimide) in acidic medium and subsequent determination of surplus oxidant by shortening of indigo carmine dye and measuring the absorbance of remaining dye at 610 nm. The absorption of residual indigo carmine is linearly and directly proportional with the concentration of trimethoprim. Beer’s law was obeyed in the range of 0.2 – 5.0 µg. ml-1 with determination coefficient of 0.9974. The molar absorptivity was 8.07×104 L.mol-1.cm-1 and sandell’s sensitivity index was 0.0035µg. cm-2, while the limit od detection (LOD) and quantitation (LOQ) were 0.0026 and 0.0089 µg. ml-1 , respectively. The proposed method was satisfactory applied for the determination of trimethoprim in available dosage form and results were compared with standard addition method.